Intervensi Latihan Fisik terhadap Perbaikan Status Frailty Pada Lansia - Kasfi, Anna; Rekawati, Etty; Rachmawati, Utami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore physical exercise interventions that can improve frailty status in the elderly. The method used was a systematic review. The results showed that 6 articles with experimental research types (Single-Arm Pre-Post Comparison Trial), and Randomized Controlled Trial which provide evidence that different physical exercise interventions can improve frailty status in the elderly, namely 1) Combination of brain and physical function training and health education, 2) Multicomponent Exercise Program (MCEP), 3) Community-based group Functional Power Training (FPT), 4) Inspiratory Muscle Training (IMT) on Whole Body Vibration (WBV), 5) Resistance Training (RT) and 6) Vitality Acupunch (VA) Exercise. In conclusion, there are six physical exercise interventions that can all be recommended to prevent and improve the frailty status of the elderly by maintaining and increasing muscle mass and function. Keywords: Older Adults, Physical Exercise, Frailty